Workplace Violence in Health Care: Current State of Affairs and Methods of Prevention - Miller, Anna N; Gutbrod, Joseph T; Taitsman, Lisa A; Samora, Julie B (Journal of the American Academy of Orthopaedic Surgeons, 2025)
Workplace violence (WPV) is a pervasive issue in health care that has shown rising incidence in recent years. There are several risk factors related to the worker, occupational environment, and patient that predispose to WPV events and should be considered in risk mitigation strategies. WPV has been associated with negative effects on worker health and professional efficacy. Past work has shown that multifactorial intervention models are more effective at improving WPV prevention and response in health care. This review summarizes the statistical trends, risk factors, and negative effects of WPV in health care, as well as interventions to improve prevention and response.